Prophetic Leadership: The Leadership Model of Prophet Muhammad in Political Relation of Social – Ummah - El Syam, Robingun Suyud (Jurnal Pendidikan Islam, 2017)
The leadership practiced by the Prophet Muhammad in the early days of Islam's birth in Madinah was a prototype of the next Muslim leadership. Therefore, it is not excessive to say that leadership in Muhammad as the bearer of Islamic mission is the masterpiece of Muhammad the founder of the foundations of Islamic leadership, which can make Madinah labeled al-Qur'an as, "Baldatun thayyibatun wa rabbun ghafūr" a good country in the pleasure of Allah. The order of the Medina state is described as "the best, just and civilized society," later termed, "civil society." The Madani community-building proved ahīh unravels the political and social problems-the the current state of affairs. Thus, it is necessary to reflect on the prophetic leadership, in order to become a role model for Islamic leadership in the present context, to solve the problems of disintegration national and disintegration.